Students' Critical Thinking Disposition in Working on Numeration Problems - Hidayanto, Erry; Dwi Cahyowati, Ety Tedjo; Ummah, Ariza Husniyatul (Jurnal Pendidikan MIPA, 2022)
This study aims to describe the critical thinking disposition of students in working on numeracy problems. This research is qualitative research with a descriptive research type. The instruments used are numeracy questions, student questionnaires, and interview guidelines. The subjects of this study were three grade IX students of one of the junior high schools in Kediri Regency, East Java, with high, medium, and low categories. The results showed that: (1) students in the high category met the indicators of critical thinking, curiosity, open-mindedness, systematic, analytical, truth-seeking, and self-confidence; (2) students in the medium category meet the indicators of critical thinking, curiosity, open thinking, systematic, and analytical; (3) students with low category meet the indicators of critical thinking, curiosity, and open thinking. Based on the results and discussion of the research, it can be concluded that all students in the  disposition, critical thinking, numeracy.Keywords: disposition, critical thinking, numeracy.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1224-1240